Stres Digital dan Gangguan Tidur: Tinjauan Literatur - Adinda Putri Salisanasti; Faras Salsabila; Afiqah Khairunnisa; Ririn Ria Riyanti; Wirza Feny Rahayu (CV. ITTC INDONESIA, 2025)
The rapid growth of digital technology has brought many benefits to daily life; however, excessive use may also lead to psychological pressure known as digital stress. One of the most frequently reported consequences of digital stress is sleep disturbance. This article aims to review the relationship between digital stress and sleep problems through a structured narrative review. Relevant studies were identified using Google Scholar and ScienceDirect databases with keywords related to digital stress, sleep quality, screen time, blue light exposure, and social media use. The search was limited to articles published within the last five years and selected based on predefined inclusion and exclusion criteria, resulting in ten eligible studies for analysis. The findings indicate that digital stress contributes to poor sleep quality through several main factors, including compulsive and excessive use of digital devices, information and social media overload, and nighttime exposure to blue light. Digital stress appears to function as a psychological mechanism that links excessive digital exposure with sleep disturbances. These results highlight the importance of healthy digital habits and balanced technology use as part of efforts to maintain sleep quality and overall psychological well-being.